HUBUNGAN SUMBER PENDAPATAN TERHADAP BELANJA MODAL PADA ANGGARAN PEMERINTAH KOTA TOMOHON - Ang, Mestika F.L; Nangoi, Grace B.; Manossoh, Hendrik (Universitas Sam Ratulangi, 2016)
In order to accomplish public service quality enhancement, the regional government is under compulsion to allocate capital expenditure in APBD to increase it’s fixed asset. Capital expenditure allocation will lead to reconcilable regional government’s fixed assets and regional civilization’s necessity. Region’s income sources is the main key of it’s financial independency without relying on central government. The main goal was to identify any firm and significant correlation between income sources and capital expenditure in Kota Tomohon’s regional budgeting while the objects were income sources and capital expenditure realization in year 2011-2015. To acknowledged these two variables’ correlation, researcher used Correlation Product Moment (Pearson) Test correlation analysis with the assistance of Software Program SPSS Version 19.0 for Windows.Correlation result 0,750 determined firm correlation between income sources and capital expenditure in Kota Tomohon since it was positive and approaching +1. It confirmed that increasing in Kota Tomohon’s income was followed by increasing in Kota Tomohon’s capital expenditure. Significancy result 0,086 validated significant correlation between these two variables as a result of it was lower or equal to 0,1 and it verified that hypothesis zero was accepted. Keywords : Correlation, Income source, Capital expenditure